Efficacy and safety of adalimumab in pediatric patients with Crohn’s disease: A systematic review and meta-analysis - Chen, Bin; Zou, Zhuan; Zhang, Xiaoyan; Xiao, Dongqiong; Li, Xihong (European journal of clinical pharmacology, 2024)
Purpose There is currently no curative treatment for childhood Crohn’s disease (CD). This meta-analysis aimed to validate the efficacy and safety of adalimumab (ADA) in pediatric patients with CD. Materials and methods We searched all relevant studies in the PubMed, Web of Science, Embase, and Cochrane Library databases. The primary outcomes were induction (≤ 12 weeks) and maintenance (up to 48 weeks) of remission and response. Secondary outcomes were severe adverse events and opportunistic infections to ADA. The Cochrane bias assessment tool was used to assess the risk of bias in randomized controlled trials. The methodological quality of the single-arm studies was assessed using the methodological index for non-randomized studies tool. Results Ten clinical trials involving a total of 885 patients were included. Results indicated that 59% (95% confidence interval [CI] 39–80%) of the subjects treated with ADA achieved induction of remission, and 60% (95% CI 35–86%) of the subjects treated with ADA achieved induction of response, 57% (95% CI 44–70%) achieved maintenance of remission, and 63% (95% CI 26–69%) achieved maintenance of response. Conclusion Current evidence indicates that ADA is effective in children and adolescents with CD and that adverse events vary but are usually not severe. Systematic review registration https://www.crd.york.ac.uk/prospero/ , identifier CRD42023402199.